Solid amine adsorbent as well as preparation method and application thereof

In the direct air trapping CO2 technology, hollow silica microspheres are used as a carrier, and the pore size and amine modification treatment are adjusted by surfactant, an efficient solid amine adsorbent is prepared, which solves the problem of low adsorption performance and achieves efficient CO2 adsorption and good stability.

CN119897073APending Publication Date: 2025-04-29INST OF COAL CHEM CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510104575.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, the adsorption performance of direct air trapping CO2 is low, mainly due to the small partial pressure of CO2 and the decrease in amine utilization rate due to amine molecular aggregation.

Method used

By placing the silicon source in a mixed solution containing phenolic resin microspheres, surfactant, ammonia water and water for hydrolysis and condensation and solid-liquid separation, hollow silica microspheres were obtained, and impregnated into a mixed solution containing surfactant, organic amine and alcohol for amine modification, a solid amine adsorbent supported by organic amine and surfactant was prepared.

Benefits of technology

This method can optimize the distribution of amine molecules, improve the amine load and adsorption properties, and achieve efficient CO2 adsorption, with an adsorption amount of 2.4 mmol/g, and the adsorbent has good stability and cycling properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897073A_ABST
    Figure CN119897073A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of adsorption materials for directly capturing CO2 from air, and particularly relates to a solid amine adsorbent as well as a preparation method and application thereof. The preparation method provided by the invention comprises the following steps: (1) putting a silicon source into a mixed solution containing phenolic resin microspheres, a surfactant, ammonia water and water, sequentially carrying out hydrolytic condensation and solid-liquid separation, and roasting the obtained solid phase to obtain hollow silicon dioxide microspheres; and (2) dipping the hollow silicon dioxide microspheres into a mixed solution containing a surfactant, organic amine and alcohol, and carrying out amine modification to obtain the solid amine adsorbent. The pore size is adjusted through the surfactant, meanwhile, distribution of amino functional groups in the structure is optimized, controllability is high, conditions are mild, raw materials are low in price and easy to obtain, operation is easy, and industrial amplification is easy to achieve.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of direct air capture CO2 adsorption materials, and in particular relates to a solid amine adsorbent and a preparation method and application thereof. Background Art

[0002] With the acceleration of human modernization, energy demand continues to increase, resulting in high CO2 emissions, exacerbating the trend of global warming. Under the current energy structure, the implementation of CO2 capture, utilization and storage is the key to achieving carbon emission reduction. As one of the CO2 capture technologies, direct air capture has the characteristics of no geographical restrictions and can solve the problem of CO2 emissions from mobile sources such as transportation. This technology has been proven to be feasible from the perspective of kinetics and thermodynamics, but in actual operation, there are still problems such as low adsorption performance due to low CO2 partial pressure. Therefore, the preparation of efficient air capture CO2 materials is of great significance to achieving carbon neutrality. Since the air components are complex in practical applications, the selectivity of the adsorbent is crucial. At the same time, the temperature and humidity in the air often affect the selectivity and purity of CO2 capture, as well as the related economic benefits. Therefore, the method of chemical directional adsorption of CO2 is often used to improve gas selectivity, which is specifically divided into solution absorption method and solid adsorption method.

[0003] Compared with the solution absorption method, the solid adsorption method has the advantages of low regeneration energy consumption and no equipment corrosion, and has attracted widespread attention from researchers. Among them, solid amines are often used as adsorbents for CO2 capture. At present, solid amine adsorbents are divided into impregnated amine-based adsorbents, grafted solid amine adsorbents and in-situ polymerization solid amine adsorbents according to different preparation methods. Among them, impregnated amine-based adsorbents have attracted widespread attention from researchers because of their simple preparation method and good adsorption performance. The impregnation method often achieves high amine loading by changing the type of amine or carrier. Commonly used amine functional groups include polyethyleneimine (PEI), polypropyleneamine (PPI), diethylenetriamine (DETA), triethylenetetramine (TETA) and tetraethylenepentamine (TEPA). Commonly used carriers include mesoporous silica (SBA-15), mesoporous silica (MCM-41) and metal organic framework (MIL-101). Among them, the adsorbent modified by TEPA impregnation shows a higher adsorption amount, such as TEPA-modified SBA-15, whose adsorption amount reaches 2.14mmol / g. However, directly modifying the support by amine impregnation will cause the aggregation of amine molecules and even block the pores of the support, thereby reducing the amine utilization rate and adsorption performance. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention provides a solid amine adsorbent and a preparation method and application thereof. The preparation method provided by the present invention can avoid amine molecule aggregation, optimize amine molecule distribution, and improve amine loading and adsorption.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a solid amine adsorbent, comprising the following steps:

[0007] (1) placing a silicon source in a mixed solution containing phenolic resin microspheres, a surfactant, ammonia water and water, and sequentially performing hydrolysis condensation and solid-liquid separation, and calcining the obtained solid phase to obtain hollow silica microspheres;

[0008] (2) The hollow silica microspheres are immersed in a mixed solution containing a surfactant, an organic amine and an alcohol to perform amine modification to obtain the solid amine adsorbent.

[0009] Preferably, the silicon source is one or more of orthosilicate and alkoxysilane.

[0010] Preferably, in step (1) or (2), the surfactant includes one or more of cetyltrimethylammonium bromide, polyethylene glycol, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer and polyvinyl pyrrolidone; the organic amine includes one or more of tetraethylene pentamine, polyethylene imine, pentaethylene hexamine, polypropylene amine, diethylene triamine and triethylene tetramine.

[0011] Preferably, the calcination temperature is 500-600° C., and the holding time is 3-6 hours.

[0012] Preferably, in step (1), the mass ratio of the silicon source to the phenolic resin microspheres is 1-4:10-20; the mass ratio of the surfactant to the phenolic resin microspheres is 1:10-20; the mass ratio of the surfactant to aqueous ammonia is 1:10-20; and the concentration of aqueous ammonia is 20%-30%.

[0013] Preferably, in step (2), the mass ratio of the surfactant to the hollow silica microspheres is 1:1-20; the mass ratio of the surfactant to the organic amine is 1:10-50; and the mass ratio of the organic amine to the alcohol is 10-50:100.

[0014] The present invention also provides a solid amine adsorbent obtained by the preparation method described in the above scheme, comprising hollow silica microspheres, and organic amines and surfactants loaded on the surfaces of the hollow silica microspheres.

[0015] Preferably, the wall thickness of the hollow silica microspheres is 20 to 90 nm.

[0016] Preferably, the content of the organic amine in the solid amine adsorbent is 30-80 wt %; the content of the surfactant in the solid amine adsorbent is 2-20 wt %.

[0017] The present invention also provides the use of the solid amine adsorbent described in the above scheme in capturing CO2 from air.

[0018] The present invention provides a method for preparing a solid amine adsorbent. The present invention adjusts the pore size of hollow silica microspheres by using surfactants, so that organic amines can diffuse more easily from the surface of the hollow silica microspheres to the inside, and optimizes the distribution uniformity of the amine functional groups in the structure, has strong controllability, and the raw materials are cheap and easy to obtain, easy to operate, and easy to achieve industrial scale-up. The present invention uses hollow silica microspheres as carriers to increase the amine loading, and the hollow silica microspheres can synergize with amine substances to increase the CO2 adsorption capacity.

[0019] The present invention also provides a solid amine adsorbent obtained by the preparation method described in the above scheme. The solid amine adsorbent provided by the present invention has high amine loading and adsorption, uniform particle size, and good stability. The data of the embodiment show that the amine-modified silica hollow sphere adsorbent prepared by the present invention achieves a CO2 adsorption amount of 2.4 mmol / g under a CO2 concentration of 400 ppm, and can be directly used for air carbon capture.

[0020] The present invention also provides the use of the solid amine adsorbent described in the above scheme in capturing CO2 from air. The solid amine adsorbent provided by the present invention has a large CO2 adsorption capacity, good adsorption effect, low regeneration temperature, and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 The scanning electron microscope images of hollow silica microspheres with different shell thicknesses in Example 1;

[0023] Figure 2 for R1-TEPA 70 -CTAB 2.5 Graph of the cyclic adsorption-desorption results. DETAILED DESCRIPTION

[0024] The present invention provides a method for preparing a solid amine adsorbent, comprising the following steps:

[0025] (1) placing a silicon source in a mixed solution containing phenolic resin microspheres, a surfactant, ammonia water and water, and sequentially performing hydrolysis condensation and solid-liquid separation, and calcining the obtained solid phase to obtain hollow silica microspheres;

[0026] (2) The hollow silica microspheres are immersed in a mixed solution containing a surfactant, an organic amine and an alcohol for amine modification to obtain the solid amine adsorbent.

[0027] The present invention places a silicon source in a mixed solution containing phenolic resin microspheres, a surfactant, ammonia water (referred to as the first ammonia water) and water (referred to as the first water) to sequentially perform hydrolysis condensation and solid-liquid separation, and then calcines the obtained solid phase to obtain hollow silica microspheres.

[0028] In the present invention, the silicon source preferably includes one or more of orthosilicate and alkoxysilane; the orthosilicate preferably includes one or more of methyl orthosilicate (TMOS) and ethyl orthosilicate (TEOS); the alkoxysilane preferably includes one or more of 3-aminopropyltrimethoxysilane (APS), methyltriethoxysilane (MTMS) and 3-aminopropyltriethoxysilane (APTES). In a specific embodiment of the present invention, the silicon source is preferably TEOS.

[0029] In the present invention, the particle size of the phenolic resin microspheres is preferably 290-500 nm, specifically 300 nm, 350 nm or 450 nm.

[0030] In the present invention, the preparation method of the phenolic resin microspheres preferably comprises the following steps: mixing (referred to as the first mixing) formaldehyde, resorcinol, ammonia water (referred to as the second ammonia water) and water (referred to as the second water) for hydrothermal reaction to obtain the phenolic resin microspheres.

[0031] In the present invention, the molar ratio of resorcinol to formaldehyde is preferably 1:10-20, specifically 1:12; the formaldehyde is preferably a formaldehyde solution; the concentration of the formaldehyde solution is preferably 35-40wt%, specifically 36wt% or 38wt%.

[0032] In the present invention, the mass concentration of the second ammonia water is preferably 20wt.% to 30wt.%, specifically 25%; the mass ratio of the second ammonia water to formaldehyde is preferably 1:2 to 5, specifically 1:2.5.

[0033] In the present invention, the mass ratio of the second aqueous ammonia to the second water is preferably 1:280-400, and specifically may be 1:300 or 1:360.

[0034] In the present invention, the first mixing is preferably: dissolving formaldehyde and resorcinol in second water and then adding second ammonia water.

[0035] In the present invention, the temperature of the hydrothermal reaction is preferably 80-120°C, specifically 80°C, 100°C or 120°C, and the insulation reaction time is preferably 12-24h, specifically 15h, 18h or 20h.

[0036] In the present invention, the mass ratio of the silicon source to the phenolic resin microspheres is preferably 1-4:10-20, specifically 1:10, 1:15, 1:20, 2:10, 2:15, 2:20, 3:10, 3:15, 3:20, 4:10, 4:15, 4:20.

[0037] In the present invention, the surfactant preferably includes one or more of cetyltrimethylammonium bromide (CTAB), polyethylene glycol (PEG), polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) and polyvinyl pyrrolidone (PVP). In a specific embodiment of the present invention, the surfactant is preferably CTAB.

[0038] In the present invention, the mass ratio of the surfactant to the phenolic resin microspheres is preferably 1:10-20, specifically 1:10, 1:15 or 1:20.

[0039] In the present invention, the mass concentration of the first aqueous ammonia is preferably 20 wt.% to 30 wt.%, and may be specifically 25 wt.%.

[0040] In the present invention, the mass ratio of the surfactant to the first aqueous ammonia is preferably 1:10-20, specifically 1:10, 1:15 or 1:20.

[0041] In the present invention, the mass ratio of the first aqueous ammonia to the first water is preferably 10 to 20:400, and specifically may be 10:400, 15:400 or 20:400.

[0042] In the present invention, the hydrolysis condensation is preferably carried out under stirring conditions; the stirring speed is preferably 500-700 rpm, specifically 600 rpm, and the stirring time is preferably 3-8 h, specifically 4 h or 7 h.

[0043] In the present invention, the solid-liquid separation is preferably filtration.

[0044] In the present invention, after the solid-liquid separation, the obtained solid is preferably dried. The drying temperature is preferably 60-120° C., specifically 100° C., and the heat preservation and drying time is preferably 8-12 h, specifically 12 h.

[0045] In the present invention, the calcination temperature is preferably 500-600° C., specifically 520° C., 550° C. or 570° C., and the insulation time is preferably 3-6 h, specifically 4 h or 5 h.

[0046] After obtaining the hollow silica microspheres, the present invention immerses the hollow silica microspheres into a mixed solution containing a surfactant, an organic amine and an alcohol for amine modification to obtain the solid amine adsorbent.

[0047] In the present invention, the surfactant preferably includes one or more of cetyltrimethylammonium bromide (CTAB), polyethylene glycol (PEG), polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) and polyvinyl pyrrolidone (PVP). In a specific embodiment of the present invention, the surfactant is preferably CTAB.

[0048] In the present invention, the mass ratio of the surfactant to the hollow silica microspheres is preferably 1:1 to 20, specifically 1:1, 1:5, 1:9, 1:10, 1:14, 1:17 or 1:20.

[0049] In the present invention, the organic amine preferably includes one or more of tetraethylenepentamine (TEPA), polyethyleneimine (PEI) and pentaethylenehexamine (PEHA). In a specific embodiment of the present invention, the organic amine is preferably TEPA and PEI.

[0050] In the present invention, the mass ratio of the surfactant to the organic amine is preferably 1:10-50, specifically 1:10, 1:20, 1:30, 1:40 or 1:50.

[0051] In the present invention, the alcohol is preferably one or both of ethanol and methanol, more preferably ethanol; the mass ratio of the organic amine to the alcohol is preferably 10 to 50:100, specifically 10:100, 15:100, 20:100, 24:100, 28:100, 30:100, 40:100 or 50:100. Alcohol is used as a diffusion solvent, so that the surfactant and the organic amine are uniformly dissolved in the solvent, which is more conducive to uniform loading of the organic amine into the hollow silica microspheres.

[0052] In the present invention, the amine modification is preferably carried out under stirring conditions; the stirring speed is preferably 600 to 900 rpm, specifically 800 rpm, and the stirring time is preferably 2 to 4 hours, specifically 3 hours.

[0053] In the present invention, the amine modification preferably further includes drying, the drying temperature is preferably 100° C., and the drying time is preferably 12 to 24 hours, specifically 15 hours or 20 hours.

[0054] The preparation method provided by the invention has cheap and readily available raw materials, mild preparation conditions, simple steps, and can realize industrial production.

[0055] The present invention also provides a solid amine adsorbent obtained by the preparation method described in the above scheme, comprising hollow silica microspheres, and organic amines and surfactants loaded on the surfaces of the hollow silica microspheres.

[0056] In the present invention, the content of the organic amine in the solid amine adsorbent is preferably 30-80 wt %, specifically 50 wt % or 70 wt %.

[0057] In the present invention, the content of the surfactant in the solid amine adsorbent is preferably 2-20 wt%, specifically 5 wt% or 15 wt%.

[0058] In the present invention, the wall thickness of the hollow silica microspheres is preferably 20-90 nm, specifically 30 nm, 50 nm or 70 nm. The present invention changes the shell thickness of the hollow silica microspheres by changing the amount of silicon source.

[0059] In the present invention, the particle size of the hollow silica microspheres is preferably 300-500 nm, specifically 310 nm, 360 nm, 400 nm, 450 nm or 480 nm.

[0060] The hollow silica microspheres provided by the present invention have suitable particle size and shell thickness, which can not only ensure the structural stability of the material, but also facilitate the diffusion of CO2 and improve the adsorption kinetics.

[0061] The present invention also provides the use of the solid amine adsorbent described in the above scheme in capturing CO2 from air.

[0062] In the present invention, the solid amine adsorbent preferably also includes desorbing the solid amine adsorbent before adsorbing CO2; the desorption is preferably carried out using argon; the desorption pressure is preferably normal pressure, the temperature is preferably 80-120°C, specifically 100°C, and the time is preferably 2-4h, specifically 3h.

[0063] In the present invention, the pressure of the CO2 adsorption is preferably normal pressure, and the temperature is preferably 60-100°C, specifically 80°C.

[0064] The solid amine adsorbent provided by the present invention has good adsorption performance and can improve the amine efficiency.

[0065] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0066] Example 1

[0067] (1) A 35 wt% formaldehyde solution and resorcinol were dissolved in H2O, with the mass ratio of formaldehyde to resorcinol being 1:3, and concentrated ammonia water (the concentration of concentrated ammonia water was 25 wt.%) was added and stirred for 12 h. The mixture was transferred into a reactor containing a tetrafluoroethylene liner and subjected to a hydrothermal reaction at 120° C. for 12 h to obtain phenolic resin microspheres.

[0068] TEOS was dissolved in a mixed solution containing phenolic resin microspheres, CTAB and H2O, and concentrated aqueous ammonia (the concentration of concentrated aqueous ammonia was 25 wt.%) was added, stirred and reacted for 6 h, filtered and placed in a constant temperature drying oven for drying (temperature was 100°C, time was 12 h), and then calcined at 550°C for 6 h to obtain hollow silica microspheres, wherein the mass ratio of CTAB:TEOS:phenolic resin microspheres:concentrated aqueous ammonia:H2O was 1:1:10:10:400, named R1, and the shell thickness of R1 was 20 nm.

[0069] (2) Dissolve a 40 wt% formaldehyde solution and resorcinol in H2O, with the mass ratio of formaldehyde to resorcinol being 1:3, add concentrated ammonia water (the concentration of concentrated ammonia water is 25 wt.%), stir for 12 h, transfer into a reactor containing a tetrafluoroethylene liner, and perform a hydrothermal reaction at 120°C for 12 h to obtain phenolic resin microspheres.

[0070] TEOS was dissolved in a mixed solution of phenolic resin microspheres, CTAB and H2O, and concentrated ammonia water (the concentration of concentrated ammonia water was 25 wt.%) was added, stirred and reacted for 6 hours, filtered and placed in a constant temperature drying oven for drying (temperature was 100°C, time was 12 hours), and then calcined at 550°C for 6 hours to obtain hollow silica microspheres, wherein the mass ratio of CTAB:TEOS:phenolic resin microspheres:concentrated ammonia water:H2O was 1:2:10:10:400, named R2, and the shell thickness of R2 was 40 nm.

[0071] (3) Dissolve a 37 wt % formaldehyde solution and resorcinol in H2O, with the mass ratio of formaldehyde to resorcinol being 1:3, add concentrated ammonia water (the concentration of concentrated ammonia water is 25 wt.%) and stir for 12 h, transfer into a reactor containing a tetrafluoroethylene liner, and perform a hydrothermal reaction at 120° C. for 12 h to obtain phenolic resin microspheres.

[0072] TEOS was dissolved in a mixed solution of phenolic resin microspheres, CTAB and H2O, and concentrated aqueous ammonia (the concentration of concentrated aqueous ammonia was 25 wt.%) was added, stirred and reacted for 6 h, filtered and placed in a constant temperature drying oven for drying (temperature was 100°C, time was 12 h), and then calcined at 550°C for 6 h to obtain hollow silica microspheres, wherein the mass ratio of CTAB:TEOS:phenolic resin microspheres:concentrated aqueous ammonia:H2O was 1:4:10:10:400, named R3, and the shell thickness of R3 was 70 nm.

[0073] Figure 1 The scanning electron microscope images of hollow silica microspheres with different shell thicknesses (R1 to R3) in Example 1 are shown in FIG. Figure 1 It can be seen that by changing the amount of TEOS added, the wall thickness of the hollow silica microspheres can be regulated, and the corresponding spherical morphology remains unchanged, while the size of the hollow silica microspheres changes slightly (300-600 nm).

[0074] Example 2

[0075] The hollow silica microspheres R1 were immersed in a mixed solution of TEPA, CTAB and ethanol, stirred for 2 h, and dried at 100 °C for 15 h to obtain a solid amine adsorbent, in which the mass ratio of CTAB:R1:TEPA:C2H5OH was 1:11:28:100, named R1-TEPA 70 -CTAB 2.5 Type adsorbent. CO2 adsorption was carried out in a fixed bed reactor. Before the reaction, the adsorbent was desorbed in an argon atmosphere at 80°C for 3 hours, and then adsorbed in a CO2 atmosphere at an adsorption temperature of 70°C and a concentration of 400ppm. The saturated adsorption capacity was measured to be 2.40mmol / g.

[0076] Figure 2 for R1-TEPA 70 -CTAB 2.5 The cyclic adsorption-desorption result diagram, from Figure 2 It can be seen that after ten cycles, the adsorption performance of the adsorbent of the present invention remains basically unchanged, indicating that the adsorbent of the present invention has good cycle performance.

[0077] Example 3

[0078] The hollow silica microspheres R2 were immersed in a mixed solution of TEPA, CTAB and ethanol, stirred for 2 h, and dried at 100 °C for 18 h to obtain a solid amine adsorbent, in which the mass ratio of CTAB:R2:TEPA:C2H5OH was 1:11:28:100, named R2-TEPA 70 -CTAB 2.5 Type adsorbent. CO2 adsorption was carried out in a fixed bed reactor. Before the reaction, the adsorbent was desorbed at 80°C and argon atmosphere for 3 hours, and then adsorbed in a CO2 atmosphere with an adsorption temperature of 70°C and a concentration of 400ppm. The saturated adsorption capacity was measured to be 1.95mmol / g.

[0079] Example 4

[0080] The hollow silica microspheres R3 were immersed in a mixed solution of TEPA, CTAB and ethanol, stirred for 2 h, and dried at 100 °C for 20 h to obtain a solid amine adsorbent, in which the mass ratio of CTAB:R3:TEPA:C2H5OH was 1:11:28:100, named R3-TEPA 70 -CTAB 2.5 Type adsorbent. CO2 adsorption was carried out in a fixed bed reactor. Before the reaction, the adsorbent was desorbed at 80°C and argon atmosphere for 3 hours, and then adsorbed in a CO2 atmosphere with an adsorption temperature of 70°C and a concentration of 400ppm. The saturated adsorption capacity was measured to be 1.81mmol / g.

[0081] Example 5

[0082] The hollow silica microspheres R1 were immersed in a mixed solution of TEPA, CTAB and ethanol, stirred for 2 h, and dried at 100 °C for 15 h to obtain a solid amine adsorbent, in which the mass ratio of CTAB:R1:TEPA:C2H5OH was 1:15:24:100, named R1-TEPA 60 -CTAB 2.5 Type adsorbent. CO2 adsorption was carried out in a fixed bed reactor. Before the reaction, the adsorbent was desorbed in an argon atmosphere at 80°C for 3 hours, and then adsorbed in a CO2 atmosphere at an adsorption temperature of 70°C and a concentration of 400ppm. The saturated adsorption capacity was measured to be 1.63mmol / g.

[0083] Example 6

[0084] The hollow silica microspheres R1 were immersed in a mixed solution of TEPA, CTAB and ethanol, stirred for 2 h, and dried at 100 °C for 15 h to obtain a solid amine adsorbent, in which the mass ratio of CTAB:R1:TEPA:C2H5OH was 1:9:30:100, named R1-TEPA 75 -CTAB 2.5 Type adsorbent. CO2 adsorption was carried out in a fixed bed reactor. Before the reaction, the adsorbent was desorbed in an argon atmosphere at 80°C for 3 hours, and then adsorbed in an adsorption temperature of 70°C and a CO2 atmosphere with a concentration of 400ppm. The saturated adsorption capacity was measured to be 2.06mmol / g.

[0085] Example 7

[0086] The hollow silica microspheres R1 were immersed in a mixed solution of PEI, CTAB and ethanol, stirred for 2 h, and dried at 100 °C for 15 h to obtain a solid amine adsorbent, in which the mass ratio of CTAB:R1:PEI:C2H5OH was 1:11:28:100, named R1-PEI 70 -CTAB 2.5Type adsorbent. CO2 adsorption was carried out in a fixed bed reactor. Before the reaction, the adsorbent was desorbed at 80°C and argon atmosphere for 3 hours, and then adsorbed at an adsorption temperature of 70°C and a concentration of 400ppm CO2 atmosphere. The saturated adsorption capacity was measured to be 1.59mmol / g.

[0087] Example 8

[0088] The hollow silica microspheres R1 were immersed in a mixed solution of PEI, CTAB and ethanol, stirred for 2 h, and dried at 100 °C for 15 h to obtain a solid amine adsorbent, in which the mass ratio of CTAB:R1:PEI:C2H5OH was 1:9:30:100, named R1-PEI 75 -CTAB 2.5 Adsorbent. CO2 adsorption was carried out in a fixed bed reactor. Before the reaction, the adsorbent was desorbed at 80°C in an argon atmosphere for 3 hours, and then adsorbed in a CO2 atmosphere with an adsorption temperature of 70°C and a concentration of 400 ppm. The saturated adsorption capacity was measured to be 1.79 mmol / g.

[0089] The adsorption test results of 400 ppm CO2 in Examples 2 to 8 are shown in Table 1, where amine efficiency = moles of CO2 / moles of N.

[0090] Table 1 Adsorption test results of 400 ppm CO2 in Examples 2 to 8

[0091] Adsorbent Content of organic amine in impregnation <![CDATA[CO2 adsorption capacity mmol / g]]> Amine efficiency Example 2 70% 2.40 0.264 Example 3 70% 1.95 0.215 Example 4 70% 1.81 0.199 Example 5 60% 1.63 0.179 Example 6 75% 2.06 0.227 Example 7 70% 1.59 0.181 Example 8 75% 1.79 0.197

[0092] It can be seen from Table 1 that the thinner shell wall of the solid amine adsorbent provided by the present invention can reduce the diffusion resistance of CO2, enhance the contact between CO2 and the amine active sites, and improve the adsorption performance of CO2. The adsorption capacity can reach up to 2.4 mmol / g under low CO2 concentration conditions.

[0093] In summary, the solid amine adsorbent prepared by coupling pore size optimization and amine loading in the present invention has a high adsorption capacity for CO2. By adjusting the preparation conditions, optimizing the size, pore size and amine loading of the hollow silica microspheres, an adsorbent with excellent performance is prepared. Among them, the hollow structure can increase the loading amount of amine substances, the thinner wall thickness can increase the CO2 adsorption and desorption rate, and the addition of surfactants promotes the improvement of pores and the distribution of organic amines.

[0094] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a solid amine adsorbent, characterized in that: The following steps are involved: (1) placing a silicon source in a mixed solution containing phenolic resin microspheres, a surfactant, ammonia water and water, and sequentially performing hydrolysis condensation and solid-liquid separation, and calcining the obtained solid phase to obtain hollow silica microspheres; (2) The hollow silica microspheres are immersed in a mixed solution containing a surfactant, an organic amine and an alcohol to perform amine modification to obtain the solid amine adsorbent.

2. The preparation method according to claim 1, characterized in that: The silicon source is one or more of orthosilicate and alkoxysilane.

3. The solid amine adsorbent according to claim 1, characterized in that: In step (1) or (2), the surfactant includes one or more of cetyltrimethylammonium bromide, polyethylene glycol, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer and polyvinyl pyrrolidone; The organic amine includes one or more of tetraethylenepentamine, polyethyleneimine, pentaethylenehexamine, polypropyleneamine, diethylenetriamine and triethylenetetramine.

4. The preparation method according to claim 1, characterized in that: The calcination temperature is 500-600° C., and the heat preservation time is 3-6 hours.

5. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the silicon source to the phenolic resin microspheres is 1-4:10-20; the mass ratio of the surfactant to the phenolic resin microspheres is 1:10-20; the mass ratio of the surfactant to ammonia water is 1:10-20; and the concentration of the ammonia water is 20%-30%.

6. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the surfactant to the hollow silica microspheres is 1:1-20; the mass ratio of the surfactant to the organic amine is 1:10-50; and the mass ratio of the organic amine to the alcohol is 10-50:

100.

7. The solid amine adsorbent obtained by the preparation method according to any one of claims 1 to 5, characterized in that: The invention comprises hollow silica microspheres, and organic amine and surfactant loaded on the surface of the hollow silica microspheres.

8. The solid amine adsorbent according to claim 7, characterized in that: The wall thickness of the hollow silica microspheres is 20 to 90 nm.

9. The solid amine adsorbent according to claim 7 or 8, characterized in that: The content of the organic amine in the solid amine adsorbent is 30-80 wt %; the content of the surfactant in the solid amine adsorbent is 2-20 wt %.

10. Use of the solid amine adsorbent according to any one of claims 7 to 9 in capturing CO2 from air.